Involvement of Transient Receptor Potential Melastatin 7 Channels in Sophorae Radix-induced Apoptosis in Cancer Cells - Sophorae Radix and TRPM7 - - Kim Byung Joo (Journal of Pharmacopuncture, 2012)
Objective:Sophorae Radix (SR) plays a role in a number of physiologic and pharmacologic functions in many organs. Methods:The aim of this study was to clarify the potential role for transient receptor potential melastatin 7 (TRPM7) channels in SR-inhibited growth and survival of AGS and MCF-7 cells, the most common human gastric and breast adenocarcinoma cell lines. Results:The AGS and the MCF-7 cells were treated with varying concentrations of SR. Analyses of the caspase-3 and - 9 activity, the mitochondrial depolarization and the poly (ADPribose) polymerase (PARP) cleavage were conducted to determine if AGS and MCF-7 cell death occured by apoptosis. TRPM7 channel blockers (Gd3+ or 2-APB) and small interfering RNA (siRNA) were used in this study to confirm the role of TRPM7 channels. Furthermore, TRPM7 channels were overexpressed in human embryonic kidney (HEK) 293 cells to identify the role of TRPM7 channels in AGS and MCF-7 cell growth and survival. Conclusions:The addition of SR to a culture medium inhibited AGS and MCF-7 cell growth and survival. Experimental results showed that the caspase-3 and -9 activity, the mitochondrial depolarization, and the degree of PARP cleavage was increased. TRPM7 channel blockade, either by Gd3+ or 2-APB or by suppressing TRPM7 expression with small interfering RNA, blocked the SR-induced inhibition of cell growth and survival. Furthermore, TRPM7 channel overexpression in HEK 293 cells exacerbated SR-induced cell death. These findings indicate that SR inhibits the growth and survival of gastric and breast cancer cells due to a blockade of the TRPM7 channel activity. Therefore, TRPM7 channels may play an important role in the survival of patients with gastric and breast cancer.